(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
With the social change the status and position of each individual change in the general public. Women, contains the greater part of the total populace, the adventure of her empowerment and strengthening from past to exhibit had not stayed consistent at a similar pace. Human rights are the verbalization of the requirement for equity, resistance, common regard, and human pride in the majority of our activity. Discussing rights enables us to express the possibility that all people are a piece of the extent of ethical quality and equity. To protect human rights is to guarantee that individuals get some degree of decent, humane treatment. To disregard the most fundamental human rights, on the other hand, is to deny people their principal moral qualifications. It is, as it were, to regard them as though they are not exactly human and undeserving of regard and dignity. Pretty much consistently there are chilling occurrences of violence, ethnic cleansing, heinous torture, youngster abuse, man slaughter and a few other human rights violations. In spite of the reception of the Universal Declaration Human Rights (1948) and exceptional agreements accommodated the rights of children, women and disabled, crimes proceed with unhindered and unabated. The spirit looking question is... ’Has humanity been surrendered?’ Maintenance is a sum payable by the spouse to his better half who is unfit to keep up herself either amid the subsistence of marriage or upon separation or divorce. The primary aim of this chapter is to discuss the law and maintenance provision of women rights and also discusses the violation related with human rights.